Peningkatan aktivitas dan hasil belajar PKn dengan pembelajaran kooperatif tipe jigsaw di kelas 8c SMP Negeri 3 Berbah - Sunarta, Sunarta (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
Classroom Action Research was conducted in class VIII C SMP Negeri 3 Berbah Academic Year 2013/2014 by using Jigsaw cooperative learning approach. This study aims to implement cooperative learning Jigsaw to improve the activity and learning outcomes of students in the subject of Citizenship Education. The method used in this study is a qualitative descriptive analysis. The results of this study indicate that prior to the implementation of the action no activity learners are categorized very active, the active category 5 (22.73%), fairly active 6 (27.27%) and less active 11 (50.00%). After the first cycle are very active category 5 (27.27%), the active category 11 (50.00%), quite active 4 (18.18%) and less active 1 (4.55). And after the second cycle which is very active category 7 (31.82%), the active category 9 (40.91%), quite active 5 (22.73%) and less active 2 (09,09%)). When viewed in the development of mastery learning it before action 9 learners otherwise completed (40.91%), following which the first cycle were 17 (77.27%) students who otherwise completed and after the second cycle students who achieve mastery learning 19 learners (86.36%). During the implementation of the action has been an increase in both, the level of activity and learning outcomes of students. Student activity levels increased along with the lessons learned in the initial group of experts and grouped. With increasing activity of the learner cognitive structure and his memory be better study results also increased